A review on image segmentation based on multi-agent systems - Amahrir, Maroua; Sabri, My Abdelouahed; Aarab, Abdellah (2017 Intelligent Systems Conference (IntelliSys), 2017)
Image segmentation has gradually become a major field of research due to the great potential it offers and the benefits it brings to different disciplines such as biology and medicine. As a matter of fact, every year new approaches tackling the problem of image segmentation are being developed whether they are based on classical segmentation techniques or on multi-agent systems. However, they are hardly assorted and classified in order to simplify research and exploration. Therefore, this paper presents a review of different image segmentation methods, though it predominantly focuses on approaches based on multi-agent systems, which enhance and simplify the process of segmentation through the inheritance of agents' characteristics and abilities as well as their interactions within the system.